An extensive in silico analysis of missense mutations of the human AIMP2 gene - Shima Farrokhi; Atieh Eslahi; Farzaneh Alizadeh; Zahra Farshchian; Yasamin Yousefi; Majid Mojarrad (Heliyon)
HLD17 (Hypomyelinating Leukodystrophy 17) is an inherited white matter disorder characterized by insufficient myelin production due to biallelic loss of function mutations in the aminoacyl-tRNA synthetase complex-interacting multifunctional protein 2 (AIMP2) gene. In silico analysis of SNVs (single nucleotide variants) in the AIMP2 gene is an efficient and cost-effective method for analyzing and predicting the impact of mutations on protein function and disease pathophysiology.The study used dbSNP and Ensembl databases to obtain data on 343 nonsynonymous single nucleotide variants (nsSNVs) in the human AIMP2 gene. Six prediction algorithm tools were used to assess the effects of these nsSNVs on AIMP2's functions and structures. Results showed that 18 nsSNVs were located within functional domains, while 10 nsSNVs led to decreased protein stability. The structural and functional properties of the AIMP2 protein were investigated using databases such as Predict Protein, Mutpred2, and HOPE. ConSurf analysis provided information about conserved nsSNVs. GeneMANIA and STRING software tools were used to predict interactions between gene-gene and protein-protein, respectively. Phyre2 and I-TASSER web servers were used to predict the 3D structures of wild-type and mutant proteins.In addition, having the challenge of probable post-translational modification sites in the AIMP2, we made predictions using various bioinformatics tools. Consecuently, three minor mutations (L138Q, V161E, and I188N) and five major mutations (C23S, D121G, I122S, P128S, and W268S) were found to affect the AIMP2 protein's structure or function. Anyway, These mutations need to be further studied and confirmed through experimental investigation and GWAS studies.